Applications of simultaneous thermogravimetry-mass spectrometry in polymer analysis - Raemaekers, K.G.H.; Bart, J.C.J.
Although thermogravimetric analysis is a powerful tool for polymer analysis its scope is limited as no information is obtained about the qualitative aspects of the evolved gases during polymer degradation. Both simultaneous and sequential techniques have been developed for identification of these gases and volatiles. Especially simultaneous TG-MS is a very powerful hyphenated technique combining the direct measurement of weight loss as a function of temperature with the use of a sensitive spectroscopic detector. In addition to the weight loss information, mass spectrometry permits temporal resolution of the gases that are evolved during thermal or thermo-oxidative degradation of a polymer in controlled atmospheric conditions. The characteristics of a broad variety of TG-MS instrumental solutions, which depend partly on the sample characteristics and the desired conditions of thermal degradation are considered, particularly in relation to polymer characterization. Advantages and limitations of TG-MS with respect to other evolved gas analysis techniques are outlined. The paper discusses the application of TG-MS in relation to the various factors affecting thermal stability of polymeric materials, thermoplastics, thermosets and elastomers. The thermoanalytical technique is used for the structural characterisation of homopolymers, copolymers, polymeric blends and composites and finds application in the detection of monomeric residuals, solvents, additives, toxic degradation products, etc. Information is also obtained on the mechanism of solid-state reactions, chemical reactivity, curing; TG-MS is also beneficial in matters of product formulation and development. The sensitivity of mass spectrometry is high enough to derive additional information about the kinetics of formation of the gases evolved from the polymer sample. Illustrative examples are given. Future prospects are outlined.
Keywords: THERMOGRAVIMETRY; MASS SPECTROMETRY; POLYMER ANALYSIS